PECULIARITIES OF LAMB WAVE PROPAGATION THROUGH TWO-LAYERED THIN PLATE MATERIALS - A. R. Baev; P. P. Prokhorenko (Наука и техника)
Peculiarities of the plate wave propagation through two-layered thin plate have been analyzed and formulas for velocity determination of the quickest plate mode have been proposed.  The ascertained interaction makes it possible   to determine coating layer thickness in accordance with the given and known elastic parameters of contacting materials. On the basis of the developed methodology experiments have been carried out that revealed qualitative and quantitative correspondence  between theoretical and experimental data. The paper shows a principle possibility for assessment  of  material separation surface by time propagation data of the investigated mode .